An efficient multiple healing conductive composite via host–guest inclusion. Issue 29 (12th March 2015) - Zhang, Da-Li; Ju, Xin; Li, Luo-Hao; Kang, Yang; Gong, Xiao-Lei; Li, Bang-Jing; Zhang, Sheng
Abstract : A self-healable conductive composite is developed by combining the small molecules and nanotubes through host–guest interactions. This material shows uniform conductivity, microwave absorption and humidity sensing properties, and can be rapidly healed to over 90% electrical and mechanical properties with the aid of water multiple times. Abstract : A self-healable conductive composite is developed by combining the small molecules and nanotubes through host–guest interactions. This material shows uniform conductivity, microwave absorption and humidity sensing properties, and can be rapidly healed to over 90% electrical and mechanical properties with the aid of water multiple times. In addition, the produced material is also remouldable and recyclable.